2024
DOI: 10.1371/journal.pone.0299384
|View full text |Cite|
|
Sign up to set email alerts
|

Immunization coverage and its associated factors among children aged 12–23 months in Ethiopia: An umbrella review of systematic review and meta-analysis studies

Alemu Birara Zemariam,
Gebremeskel Kibret Abebe,
Mulat Awoke Kassa
et al.

Abstract: Background Immunization estimated to prevent 2 to 3 million children deaths every year from vaccine preventable disease. In Ethiopia, limited and inconclusive studies have been conducted on immunization coverage so far. Therefore, this umbrella review was intended to estimate the pooled national immunization coverage and its associated factors among children age 12–23 months in Ethiopia. Methods This umbrella review included five systematic reviews and meta-analyses through literature search from PubMed, Sci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…In response to this pressing issue, the Ethiopian government designed and implemented various strategies. These included mobilizing volunteers, health extension workers, and healthcare facilities to expand immunization services, with the aim of substantially reducing morbidity and mortality among children under five from vaccine-preventable diseases ( 8 , 10 ). Following to these efforts, there has been a slight improvement in immunization coverage ( 8 , 11 ), with a noteworthy reduction in under-five mortality rates ( 11 , 12 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In response to this pressing issue, the Ethiopian government designed and implemented various strategies. These included mobilizing volunteers, health extension workers, and healthcare facilities to expand immunization services, with the aim of substantially reducing morbidity and mortality among children under five from vaccine-preventable diseases ( 8 , 10 ). Following to these efforts, there has been a slight improvement in immunization coverage ( 8 , 11 ), with a noteworthy reduction in under-five mortality rates ( 11 , 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Various interconnected and interrelated individual, community, and service delivery-related factors affect the childhood immunization level in the country. Existing literature has primarily shown that individual-level factors, including mothers' educational status, antenatal care follow-up, place of delivery, postnatal care, residence, media exposure, and wealth level, play a significant role in determining the level of childhood immunization ( 10 , 14 20 ). In contrast, the influence of community-level factors on incomplete immunization has not been adequately investigated in Ethiopia.…”
Section: Introductionmentioning
confidence: 99%